The Management of Catatonia in Bipolar Disorder with Stimulants - Waheed K. Bajwa; Ali Rastegarpour; Omar A. Bajwa; Jessica Babbitt (Case Reports in Psychiatry)
Catatonia, while not a rare occurrence in bipolar disorder, has not been widely discussed in the literature. We present a case of a married Caucasian male with a history of bipolar disorder, exhibiting catatonia and experiencing difficulty in day-to-day functioning. He demonstrated impairment in cognition and an inability to organize simple activities of daily life. After exhausting a number of options for medical management, including benzodiazepines, atypical antipsychotics, and amantadine, he only displayed significant clinical improvement with the addition of a stimulant, methylphenidate. In time, the patient saw a complete return to normal functioning. The use of stimulants for catatonia in bipolar disorder may be an interesting and effective option for treatment. While this is not the first time this treatment has been suggested, there is very little data in support of it; our case confirms the discoveries of previous case reports.